Phytoremediation of a Polluted Soil by Purple Plant (Tradescantia pallida L.) Under Different Organic Amendments - Khudhur, Nashmeel (Al-Qadisiyah Journal of Pure Science, 2021)
Present investigation was performed to determine the ability of purple plant (Tradescantia pallida L.) for removing heavy metals from a contaminated soil particularly nickel, with the aid of different types of organic amendments. Results of soil heavy metal content after application of different fertilizers were: maximum values (ppm) of V, Cr, Ni, Mn, Cu, Zn, As, Mo, Cd, Pb and Ag were respectively: 275.437, 284.807 (control 1), 265.073, 1071.32, 60.0671 (control 2), 77.8288, 9.5162, 8.5267 (control 1), 5.7943 (control 1), 7.5076 (control 2) and 37.8868 (control 1). Whereas, the minimum values (ppm) of V: 104.644, Cr: 85.7222 (commercial fertilizer), Ni: 164.92, Mn: 711.155 (cow dung), Cu: 15.5141 (cow dung), Zn: 43.3929 (commercial fertilizer), As: 3.7819 (cow dung), Mo: 0.000 (plant residue composite and bird manure), Cd: 0.000 (plant residue composite and bird manure), Pb: 4.1535 (bird manure) and Ag: 2.9181 (plant residue composite). This indicate that the use of organic amendment induce the phytoremediation of polluted soils.